Plan estratégico para el almacén de motos “Motofox”, de la ciudad de Loja período 2016-2021 - Ruíz Luna, Katty del Cisne (2017)
The present research is entitled: "STRATEGIC PLAN FOR MOTORCYCLE ALMACEN "MOTOFOX" OF THE CITY OF SHOP, PERIOD 2016 - 2021", the general objective of the present investigation is to elaborate a Strategic Plan for the Motorcycle Company "MOTOFOX "in the City of Loja, which will provide valuable knowledge for the company" MOTOFOX "in improving its application of planning strategies. In the first place, different methods were determined using the Inductive method, which allowed to establish the reality found in the motorcycle company “MOTOFOX” from the particular to the general, the Statistical method, facilitated the tabulation of the applied surveys To the external clients of the company, as well as to the employees and Manager of the company; Within the techniques allowed to apply the survey to the clients, employees and an interview with the Manager of the company “MOTOFOX”, in these conditions said data collaborated to be able to formulate the strengths, opportunities, weaknesses and threats, always supporting in the investigation of Field, in the design of the SWOT matrix, which allowed the deduction of the Mission and Vision, the establishment of objectives, strategies, tactics, goals that allowed to establish the conclusions and recommendations that the project has and the solutions that are Established for the parameters described in the proposed strategic plan, the Analytic - Synthetic method allowed to make the conclusions and recommendations for its particularity of description; Within the techniques, a survey was applied to the clients, employees and an interview with the Manager of the company, under these conditions these data collaborated to be able to formulate the strengths, opportunities, weaknesses and threats, always relying on field research, Design of the SWOT matrix. The internal and external analyzes were then performed through the application of the EFE matrix, where the weighting was assigned for each of the external factors influencing the company "MOTOFOX", in which we obtained the weighted result of 2.43 Which means that there is a predominance of threats over opportunities; In the EFI matrix, the weighting was assigned for each of the internal factors that influence the company, resulting in the result of 2.55 which means that the company has a predominance of strengths over weaknesses, The analysis of the Mission and Vision to later rethink the Vision, Mission, Objectives. With these considerations through the Matrix of High Impact, five strategic objectives were proposed, among which it is determined, Promote and reinforce the marketing channel of the company whose budget is $ 7.190,00 dollars annually. Among the most important conclusions, it is determined that based on the interviews, surveys, managers, workers and clients of the company, it is determined that it does not have a Strategic Plan, which allows to improve the products and services to the clients, if Makes it necessary to strengthen and implement new strategies to face them; The workers stated that there is no strategic plan for the company to improve the performance of employees to fulfill the tasks, activities and functions in the company; The Manager of the company, state that there is no strategic plan in the company; Employees say that the company does not have promotions to attract customers.